Governance: Exploring the Islamic Approach and its Relevance for the Modern Context - Mohammed Veqar Ashraf-Khan; Mohammad Shahadat Hossain (UIN Sunan Gunung Djati Bandung, 2021)
Managing this wealth (amanah) leads to the basic concept of Islamic accountability where proper disclosure and transparency in every business transaction or service is encouraged. This paper attempts to explore the characteristics and application of the principles of Islamic governance. Using qualitative research methods, this study further focuses on trust and accountability with respect to governance mechanisms as required by Islamic principles and in light of today's world affairs. As a doctrinal research, the researcher reviews the relevant literature to identify the main features of government such as shura, caliphate, accountability, transparency, justice and equality as well as the current need for trust in public and private government. The findings of this study are that the Koran and the Sunnah of the Prophet Muhammad (SAW) have provided many guidelines in the field of constitutional affairs that can help the government system. The Qur'an is flexible enough not to mention the details and details that are left for Muslims to formulate according to their particular circumstances. Finally, the aim of this paper is to inform policy makers and practitioners about the main doctrines that have been proposed by the Qur'an and which can be applied for the effective management of our affairs